FIRST AID IN THE LESSON PROCESS AND ITS SIGNIFICANCE - Rishad Badaev (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. The article reveals the features of first aid that every person in our society should know how to provide first aid to himself and others, and proper first aid, provided in a timely manner, will save the lives of a large number of people